Frontonasal Encephalocele: A Case Report - Aydın, Mustafa; Taskın, Erdal; Kılıç, Mehmet; Ertuğrul, Sabahattin; Aygün, Denizmen (Fırat University, 2005)
A 6-month-old girl who diagnosed frontonasal encephalocele is presented. She was referred to our hospital with a swelling on the glabella. She had a swelling over the glabella, 2x3 cm in diameter not associated with cerebrospinal fluid (CSF) leakage. A magnetic resonance imaging and threedimensional computed tomography scan showed frontal bony defect and brain herniation from this defect (anterior encephalocele). Especially, the encephaloceles with CSF leakage must be followed up closely for the occurence of meningitis; and if required the surgical treatment must be done for reconstruction ©2005, Fırat Üniversitesi, Tıp Fakültesi

Alın üzerinde şişlik şikayeti ile başvuran ve frontonazal ensefalosel tanısı alan 6 aylık kız hasta sunuldu. Muayenesinde, glabella üzerinde beyin omurilik sıvısı (BOS) sızıntısı olmayan, 2x3 cm ebadında bir şişlik vardı. Manyetik rezonans görüntüleme ve üç boyutlu bilgisayarlı tomografi, frontal kemik defekti ve bu defektten beyin herniyasyonunu gösterdi (anterior ensefalosel). Özellikle BOS sızıntısı eşlik eden ensefaloseller menenjit gelişimi açısından yakından izlenmeli; gerekirse cerrahi tedavi ile onarım operasyonu yapılmalıdır. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Frontonazal Ensefalosel: Bir Vaka Takdimi